Programa ler e escrever: a formação sob a perspectiva das alunas pesquisadoras - Liberato, Amanda Maria Franco (2015)
The object of this research is the formation of the student researcher under the perspective of these actors. The general purpose was to analyze the formation under the perspective of students’ researchers in three Institutions of Higher Education (IHE) partners of the Program Read and Write / Public School and University in Literacy / Literacy Exchange of the Government of the State of São Paulo. As specific objectives we listed the following: check if the student researcher develops activities to be delivered in training meetings and verify the students researchers if the advisor professors allow moments of exchange of knowledge coming from the practice in training meetings. Our hypothesis is that the formation of the student researcher does not occur effectively by some IHEs contrary the guidelines established by the official program and thus we seek to answer the following questions: How goes the training of students researchers in universities? How often? What are the topics covered in this training? Discussions allow the student researcher relates theory and teaching practice and takes ownership of the fundamentals of literacy? The training allows the stage in literacy courses is experienced from another viewpoint? Which? The universe of the research were three private IHEs located in São Paulo city whose subjects were six students researchers that study Pedagogy, from two of each institution. We used qualitative matrix method using a semi-structured interview as data collection instrument, as well as analysis of official documents governing this Program, namely: Communication SE 86, 2007; Resolution SE 86, 2007; Decree No. 51627, 2007, and Resolution SE 90, 2008. We have analyzed the interviews using the content analysis according to Bardin (2011). The research was based on the following authors: Ferreiro (1995 and 2003); Lerner (1995 and 2002) and Smith (1985, 2009 and 2011) in order to support the categories alphabetization and literacy; Contreras (2012), Nóvoa (1992) and Tardiff (2002) to reference the initial category of teacher education. As a result the researchers found that students in school A and B receive training more focused on administrative aspects, with few hours of study and reflection hindering the assessment of the basic concepts related to the literacy process, showing unsafe when immersed in school while the students researchers of the university C receive more geared to the pedagogical aspects of training, enabling them to have greater contact with the authors who discuss literacy in a constructivist perspective leading them to a better understanding of the concepts and therefore the procedures adopted by the regents teachers. We conclude that the students researchers from colleges A and B require theoretical study about the concepts related to literacy for better performance in the classroom.